2020
DOI: 10.3390/jcm9041122
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment on Subungual Osteochondromas in Paediatric Feet: A Case Series Study

Abstract: Subungual osteochondroma (SO) is an infrequent and non-malignant bone tumour of the distal phalanx, especially prominent in paediatric populations. The aim of this research was to describe a case series of paediatric feet with SO which received surgical treatments. The secondary purpose was to compare these descriptive data by sex distribution. Methods: Twenty-three paediatric feet with SO confirmed by clinical or radiological features received surgical treatment. Socio-demographic (age, sex, height, weight an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…All studies showed a predominance of the defect in the big toe [7,27]. In children populations with SE, the defect was located in the big toe in 75% of the cases and the second toe in 20% of the cases [4].…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…All studies showed a predominance of the defect in the big toe [7,27]. In children populations with SE, the defect was located in the big toe in 75% of the cases and the second toe in 20% of the cases [4].…”
Section: Discussionmentioning
confidence: 89%
“…In a pediatric population, SE was located in the big toe in 55% of cases, in the second or third toes in 30% of the cases and the distal phalanxes of the fingers in only 7.5% of the cases-twice as often on the right side [22]. The most frequent locations of SO in children were the first toe (86.8%) and the right lower limb (56.5%) [27].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…So far, no single or combined drug treatment can cure MPNST and a complete surgical resection remains the only treatment option for MPNST patients [30]. The success rate of surgical resection of the low risk tumor located at the end of the limb is greatly increased [31]. However, in patients with high-risk soft tissue sarcoma of the trunk and limbs, neoadjuvant therapy is associated with recurrence-free survival and overall survival when the tumor is ≥ 10 cm [32].…”
mentioning
confidence: 99%